Pengaruh online customer review dan product quality terhadap purchase decision dengan brand trust sebagai variabel mediasi pada produk facial wash MS Glow - Galih Arum Anggraini; Nindria Untarini (Jurnal Ilmu Manajemen, 2025)
The shifting position of MS Glow in the local beauty industry reflects significant competitive dynamics. The brand ranked first in 2022, dropped to second place in 2023, and fell to fourth place by mid-2024. This decline was influenced by customer complaints related to prolonged acne, decreased product quality, and the growing reliance on online reviews in purchasing decisions. This study aims to analyse the influence of online customer reviews and product quality on purchase decisions, with brand trust as a mediating variable, focusing on MS Glow facial cleanser products. A quantitative approach was employed by distributing questionnaires to 220 female respondents aged 18–35 who purchased the products through online stores. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 3.0. The results indicate that online customer reviews have a positive but insignificant impact on brand trust, whereas product quality has a positive and statistically significant effect on brand trust. Both online reviews and product quality have a positive and significant effect on purchase decisions, as does brand trust. Brand trust does not mediate the influence of online reviews on purchase decisions but does mediate the influence of product quality on purchase decisions. Managerial implications suggest that MS Glow should prioritise consistent product quality improvement to strengthen brand trust and encourage purchases. Strategic management of online reviews remains essential to building a positive brand image, alongside prompt responses to customer complaints to maintain loyalty in a competitive market.